Positive communication in preventing bullying among students at Al Fazhira Integrated Islamic Elementary School [komunikasi positif dalam mencegah bullying bagi siswa SD Islam Terpadu Al Fazhira] - Dwianita; Ira Nur Dewita Siregar; Yohana Yulianti Simbolon (LPPM Universitas Syiah Kuala, 2025)
Bullying is a serious problem in elementary schools that can affect the mental state and social relationships of students. This service program aims to apply good communication as a way to prevent bullying at Al Fazhira Integrated Islamic Elementary School, especially in the case of a student with special needs who feels excluded because he is a victim of bullying. The methods used include direct observation, discussion with teachers, identification of needs, and conducting interesting and interactive socialization for 5th grade students with the use of films, posters, and discussions. Five aspects of positive communication were introduced, namely openness, empathy, support, positive attitude and equality. The results of this activity showed that students became more aware of the impact of bullying, dared to report if there was an incident, and had a better sense of empathy. The teachers also responded favorably and were willing to incorporate this approach into their teaching and learning activities. It can be concluded that positive communication is effective in creating an inclusive and safe school environment through early detection, reducing power differentials, and empowering victims and witnesses of bullying.